Phenetic and Functional Analyses of the Distal Ulna of Australopithecus afarensis and Australopithecus africanus. Issue 1 (January 2015) - Tallman, Melissa; Terhune, Claire; Cooke, Siobhán B.; Laitman, Jeffrey T.
ABSTRACT The morphology of the distal portion of the hominoid ulna is poorly studied despite its important functional role at the wrist joint. There are five qualitatively well‐described fossil hominin distal ulnae belonging to Australopithecus afarensis and Australopithecus africanus, but there have been few efforts to quantify their morphology or relate it to their functional abilities. This article presents an effort to do so, using three‐dimensional geometric morphometrics to analyze the shape of the distal ulna of the Plio‐Pleistocene hominins and an extant comparative sample of great apes and humans. For the extant taxa, results show that the morphology of Pan and Pongo is distinct from that of Homo, and that these differences are likely related to climbing, clambering and below‐branch suspension in the former, and the release of the limbs from locomotion and (potentially) tool manufacture in the latter. For the australopiths, results indicate that the A. afarensis sample is relatively heterogeneous. These results are driven by the morphology of A.L. 333‐12, which is the largest ulna in the sample and has a unique combination of traits when compared with the other two A. afarensis specimens. Overall, the morphology of all the hominins was most consistent with the pattern displayed by extant great apes, and specifically Pan and Pongo; however, large overlap in shape in the distal ulna in the extant sample indicates that other areas of the skeleton may be more informative for functional analyses. Anat Rec, 298:195–211, 2015. © 2014 Wiley Periodicals, Inc.